Analisis Persepsi Followers Instagram Akun @marioteguh Mengenai Personal Branding Mario Teguh Pasca Kasus Pengakuan Anak Kandung oleh Kiswinar - Deandra Shivana; Soraya Nurida; Joe Harrianto Setiawan (COMMENTATE: Journal of Communication Management, 2021)
This research study is conducted with the objective to learn about the analysis of public’s perception from Mario Teguh’s personal branding that was taken from the Instagram followers of @marioteguh after the case of Kiswinar who claimed to be his biological son came to the public’s attention on 2016. The main theory used is Personal Branding Concept and the method that’s used is qualitative method. Data collective is through whatsapp interview. Based on this research study, Mario Teguh has two from three elements of personal branding which are clarity and specialization but failed to obtain the consistency element because of the difference between his personal branding and the reality after the case of Kiswinar.